Anderson localization of light in disordered superlattices containing graphene layers - Chaves, A. J. (2015)
We theoretically investigate light propagation and Anderson localization in one-dimensional disordered superlattices composed of dielectric stacks with graphene sheets in between. Disorder is introduced either on graphene material parameters ({\it e.g.} Fermi energy) or on the widths of the dielectric stacks. We derive an analytic expression for the localization length $ξ$, and compare it to numerical simulations using transfer matrix technique; a very good agreement is found. We demonstrate that the presence of graphene may strongly attenuate the anomalously delocalised Breswter modes, and is at the origin of a periodic dependence of $ξ$ on frequency, in contrast to the usual asymptotic decay, $ξ \propto ω^{-2}$. By unveiling the effects of graphene on Anderson localization of light, we pave the way for new applications of graphene-based, disordered photonic devices in the THz spectral range.